An efficient edge-functionalization method to tune the photoluminescence of graphene quantum dots. Issue 14 (17th March 2015) - Qi, Bao-Ping; Hu, Hui; Bao, Lei; Zhang, Zhi-Ling; Tang, Bo; Peng, Ying; Wang, Bao-Shan; Pang, Dai-Wen
Abstract : A simple but efficient method is developed to modify the edge of GQDs, causing the photoluminescence of GQDs to be regularly red-shifted. Abstract : An efficient edge-functionalization strategy with high specificity was employed to study the effects of conjugated structures on photoluminescence (PL) properties of graphene quantum dots (GQDs). Both the experimental results and density functional theory (DFT)-based calculations suggested the mechanism for conjugated structures in GQDs to tune the band gap of GQDs.